2010
DOI: 10.1021/jf103439c
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Irradiated Prawn (Penaeus monodon) Using Thermoluminescence and 2-Alkylcyclobutanone Analyses

Abstract: Thermoluminescence (TL) and 2-alkylcyclobutanone (2-ACB) analyses were performed to identify irradiated prawns ( Penaeus monodon ). With the TL method, minerals were extracted from prawns using acid hydrolysis. The experimental results satisfied the evaluation criteria of European Norm (EN) 1788, even after low-dose irradiation (0.5 kGy) and a 60 day storage at -20 °C. With the 2-ACB method, 2-dodecylcyclobutanone (2-DCB) and 2-tetradecylcyclobutanone (2-TCB) were successfully extracted from prawns by direct s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The extraction efficiency of hexane applied to prawns by shaking was studied by Chen et al (2011) who found that three sequential extractions were required for optimum recovery.…”
Section: Direct Solvent Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extraction efficiency of hexane applied to prawns by shaking was studied by Chen et al (2011) who found that three sequential extractions were required for optimum recovery.…”
Section: Direct Solvent Extractionmentioning
confidence: 99%
“…Further clean-up has been achieved by using a Supelclean TM sulfoxide column following a silica column for the determination of 2-ACBs in irradiated prawns (Chen et al, 2011). 2-ACBs were selectively eluted from the sulfoxide column and impurities removed from the GCMS chromatogram.…”
Section: Clean-up Proceduresmentioning
confidence: 99%
“…At the end of the 90-day oral toxicity test, retroperitoneal adipose tissue was removed from 6 males and 3 females during autopsy, weighed and then stored at −80°C until use. Briefly, adipose tissue was homogenized with anhydrous sodium sulfate and extracted with n -hexane in a Soxhlet apparatus for 6 h. Concentrations of 2-tDCB in hexane extracts were analyzed using a GC-MS system (QP2010 Plus, Shimadzu, Kyoto, Japan) as per a previously described method 17 .…”
Section: Methodsmentioning
confidence: 99%
“…For example, the test solutions may have to be concentrated. 11 DNA is universally contained in the low-fat liver and lean meats, and its content would not be affected by the difference of individual of animals. Therefore, we have developed and presented a new method for determining beef liver irradiation histories by detecting of the sum of (5 S )- and (5 R )-5,6-dihydrothymidine (total DHdThd) as irradiation-induced modified nucleosides in DNA.…”
Section: Introductionmentioning
confidence: 99%